2016
DOI: 10.1002/humu.23026
|View full text |Cite
|
Sign up to set email alerts
|

Mutation Update for Kabuki Syndrome GenesKMT2DandKDM6Aand Further Delineation of X-Linked Kabuki Syndrome Subtype 2

Abstract: Kabuki syndrome (KS) is a rare but recognizable condition that consists of a characteristic face, short stature, various organ malformations, and a variable degree of intellectual disability. Mutations in KMT2D have been identified as the main cause for KS, whereas mutations in KDM6A are a much less frequent cause. Here, we report a mutation screening in a case series of 347 unpublished patients, in which we identified 12 novel KDM6A mutations (KS type 2) and 208 mutations in KMT2D (KS type 1), 132 of them nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
170
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(183 citation statements)
references
References 66 publications
(138 reference statements)
11
170
2
Order By: Relevance
“…KDM6A is a lysine specific histone demethylase that controls tissue-specific expression of genes involved in development as well as the cell cycle [3438]. Loss of function mutations of KDM6A which cause Kabuki Syndrome Type 2, KS2, are most often somatic mutations [18, 20, 2225, 27]. Arnoux, et al, reported that hypoglycemia occurs in 11% of Kabuki Syndrome patients overall [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…KDM6A is a lysine specific histone demethylase that controls tissue-specific expression of genes involved in development as well as the cell cycle [3438]. Loss of function mutations of KDM6A which cause Kabuki Syndrome Type 2, KS2, are most often somatic mutations [18, 20, 2225, 27]. Arnoux, et al, reported that hypoglycemia occurs in 11% of Kabuki Syndrome patients overall [39].…”
Section: Discussionmentioning
confidence: 99%
“…Arnoux, et al, reported that hypoglycemia occurs in 11% of Kabuki Syndrome patients overall [39]. Recent reports suggest that hypoglycemia may occur in a much higher proportion of patients with KS2 associated with KDM6A mutations [13, 20, 22, 26]. The mechanism by which haploinsufficiency for KDM6A causes hyperinsulinism in Kabuki Syndrome is not known, but has been suggested to involve disruption of epigenetic changes during pancreatic differentiation [28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…After BWS, Kabuki syndrome is the second most common syndromic form of HI. Kabuki syndrome is caused by inactivating mutations in 2 genes: autosomal recessive mutations in KMT2D ( Lysine‐specific methyltransferase 2D ), which account for 70%‐75% of cases, and X‐linked mutations in KDM6A ( Lysine‐specific demethylase 6A ), which account for 1%‐9% of cases. These 2 genes encode a DNA methyltransferase and demethylase, respectively.…”
Section: Highlights From the Conferencementioning
confidence: 99%
“…Heterozygous or hemizygous, pathogenic variants in either KMT2D (OMIM: 147920; 80% of cases) or KDM6A (OMIM: 300867; 8%), respectively, cause Kabuki syndrome (Banka et al, ; Bogershausen et al, ; Lederer et al, ; Miyake et al, ; Ng et al, ; Van Laarhoven et al, ). KMT2D encodes a H3K4 methyltransferase that associates with KDM6A, an H3K27 demethylase, and other proteins to form the activating signal co‐integrator 2 containing complex (ASCOM) responsible for chromatin regulation and transcription activation where loss of function leads to repressed transcription in a wide range of downstream genes (Demers, Chaturvedi, Ranish, et al, ; Van Laarhoven et al, ).…”
Section: Introductionmentioning
confidence: 99%